A nomenclatural note in Cimicidae (Hemiptera) from South America - Iorio, Osvaldo R. Di; Turienzo, Paola N. (Zootaxa, 2008)
Cordero & Vogelsang (1928) described Cimex furnarii found in nests of Furnarius rufus [rufus (Gmelin, 1788)] (Aves: Furnariidae), from Uruguay. In the same work, Cimex passerinus, found once in nests of Passer domesticus (L., 1758) [Aves: Ploceidae], was briefly described and illustrated; type-repository and number of specimens were not given. Carvalho (1939) includes Cimex furnarii in the genus Ornithocoris Pinto, 1927 [type-species: O. toledoi Pinto, 1927 by monotypy].